Republic of Slovenia : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Republic of Slovenia, being the most successful transition economy in Central and Eastern Europe, has achieved significant economic convergence with the European Union, and has built up an impressive record of sustained, broad-based growth, reflecting strong competitiveness and investment. However, Executive Directors emphasized the need to maintain strong monetary and fiscal policies, and accelerate structural reforms. They commended the comprehensive action plan prepared by the authorities to strengthen prudential standards, improve liquidity management, and deepen the money market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet